DAVIANT BEHAVIOR AMONG SERVICE MEN - Nadoyan, A.A.; Minasyan , G. G. (Արդի հոգեբանություն, 2021)
The article discusses the main issues of deviant behavior among servicemen, causes of changes of their behavior, also norms of behavior in Armenian army. One of the issues of our research program is directed to servicemen’s deviant behavior, which is connected to aggressiveness and self-esteem. The quality of servicemen’s professional 382 activities and their behavior directly depends on the level of their psychological health, preservation and strengthening of which is one of the most important directions in the work of military psychological services.